Deforestation in Indonesian and Malaysian Novels: When Wild Forests are Destroyed by Anthropocentricism - Wiyatmi Wiyatmi; Else Liliani; Esti Swatika Sari; Mawar Safei (k@ta: A Biannual Publication on the Study of Languange and Literature, 2022)
Anthropocentrism is one of the perspectives applied in figuring out human relations with the environment. The environmental crisis happening in most areas of the world lately is allegedly the impact of anthropocentrism, which views humans as the center of the universe, and only humans have the right to utilize and make use of nature for their interests and needs. One of the environmental crises which hit the world today is deforestation. The description of deforestation and its various consequences can be looked through not only from the news in mass media or research reports, but also from Indonesian and Malaysian novels. This study aims at examining the issue of deforestation described in Indonesian and Malaysian novels. The method applied is a comparative qualitative descriptive with an ecocritical perspective. As data sources, two Indonesian novels and two Malaysian novels were selected, namely Api Awan Asap (Rampan) and Tanah Tabu (Thayf) as the samples of Indonesian novels; Penunggu Rimba: Tombiruo (Mursid) and Anak Belantara (Abdullah) as the samples of Malaysian novels. From an eco-critical perspective, the results of the study show that in the four novels studied, it appears that there is an issue of deforestation in Indonesia and Malaysia which has resulted in various other environmental problems. The four analyzed novels reveal how local wisdom can prevent and fight deforestation which occurs in the forests of Kalimantan and Papua. Added to this, through the novels, Indonesian and Malaysian writers both present ecocentrism perspectives to fight anthropocentrism which causes deforestation. Some different views are expressed by Indonesian and Malaysian writers in dealing with deforestation.